Reducing Emissions from Deforestation and Degradation: Some Issues and Considerations - Adhikari, Bhim (Journal of Forest and Livelihood, 2009)
Forest commons are crucial for delivering a wide range of socio?economic and environmental benefits such as contribution to rural livelihoods, biodiversity conservation and carbon sequestration. Yet, a large proportion of the existing scholarly and policy literature on forest commons has been historically guided towards the direct benefits, but less on multiple outcomes of forest ecosystems. This review paper advances the argument for an integrated analysis of major ecosystem services provided by forest commons in order to make sure that any intergovernment negotiations on forest and climate change such as Reducing Emissions from Deforestation and Degradation (REDD) would not miss the importance of either component. The paper also provides a review on the global carbon market and the Clean Development Mechanism (CDM) as well as some international insights on REDD. Key words: climate change, ecosystem services, REDD, forest commons, adaptation, biodiversity, livelihoods Full text is available at the ForestAction website Journal of Forest and Livelihood 8(1) February 2009 pp.14-24